Polyglycerol/Polydopamine-Coated Nanoparticles for Biomedical Applications - Sotoma, Shingo (Frontiers in Materials, 2022)
Nanoparticles play an active role in biomedical science due to their unique properties, which cannot be obtained from bulk materials. Therefore, understanding and controlling the physicochemical properties of nanoparticles are gaining increasing importance for their practical applications. Surface coating is an important technique that controls the physical properties of nanoparticles since the coating is the first part of the nanoparticle that is in contact with the environment. Additionally, the coating creates robust targeting, therapy, imaging, and sensing opportunities. This review first introduced two recently developed outstanding coatings, namely, hyperbranched polyglycerol and polydopamine, and the research achieved by the polyglycerol/polydopamine-coated nanoparticles was then highlighted.